Antihypertension medication adherence and associated factors at tertiary care hospital, Gujarat, India - Goswami, Dinkar (International Journal of Advances in Medicine, 2019)
Background: According to world health organization (WHO) describes poor adherence as the identical cause of uncontrolled blood pressure and estimates that 50-70% of people do not take their antihypertensive medication as prescribed. The objectives of this study were to investigate the adherence and persistence of antihypertensive drugs in Indian rural population as well as monitoring adverse drug reactions and its relation to compliance. Methods: This cross-sectional study conducted among 300 hypertensive patients taking treatment at tertiary care hospital in Gujarat, India. Structured questionnaires consisting of open and closed ended questions on the antihypertensive drug adherence were distributed to patients for those found on the study area at time of data collection and the left-over pills of individual patient were counted to strengthen the consistency of the research. Results: Prevalence of non-adherence found in 24.3% participants. Present study found statistically significant association between socio-demographic factors (age, religion, marital status, occupation, substance abuse, education and family history of HT) with treatment adherence of hypertension among study participants. The other factor associated to non-adherence was therapy factor 32.9% (P=0.001) from the total non-adherence, in this case patients were supposed to unwanted effect of the drug and they were not able to take the medication. Conclusions: The main possible reasons for non-adherence were ‘refuse to take regular treatment’,‘cost of treatment’, ‘poor patient-doctor relation’, ‘unwanted side effect of drugs’ and other factors like age, marital status, occupation, education level, family H/O, substance abuse and religion are also playing supporting role to develop non-adherence to treatment.